The Android Based Social Welfare Survey Application - Moh Anshori Aris Widya; R Abdullah Hammami (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Socioeconomic welfare is a complex problem, so more work is needed to address the lack of population welfare. One way by reviewing communities by surveying methods is that the survey method itself has the advantage that the results of the survey can be translated into number and this can make it easier for data grouping. But the current system of surveying is conducted has many flaws, ranging from an easy to split-down survey sheet damaged to difficult recapitulation because data must be regenerated. Lacking the conventional survey system, it is necessary for a system that can solve the problems that arise and enable survey activity to run smoothly. Researchers choose Research and Development Method. The goal of this study is to produce an app that can be used on an android device. The framework base researcher use is Framework7. Framework7 is the choice because framework7 have user friendly interface characteristics. The development of the conventional survey system is an android - based application for the social welfare of the population to make it easier for officials to survey in the field and help village staff to log the survey data, so that it can be reported to the data center.